Plant synthetic biology: from knowledge to biomolecules - Park, Soyoung; Mani, Vimalraj; Ha, Kihun; Kim, Jin A.; Lee, Sichul (Frontiers in Plant Science, 2025)
Plant synthetic biology is rapidly emerging as an innovative approach to solving complex problems in human health and agriculture. Although conventional metabolic engineering primarily focuses on microbial systems for large-scale biomolecules production, these platforms often face limitations in expressing plant-derived enzymes and synthesizing structurally complex molecules. In contrast, recent advances in plant synthetic biology have integrated multidisciplinary tools, from molecular biology and biochemistry to synthetic circuit design and computational modeling, to engineer plant systems with enhanced traits. These include improved yield, nutritional quality, environmental resilience, and synthesis of pharmaceutically relevant functional biomolecules. This review focuses on the fundamental technologies that have enabled such advances, which include DNA synthesis, programmable gene circuits, and CRISPR/Cas-based genome editing. We discussed recent applications of reprogramming plant metabolic pathways and existing obstacles, such as transformation efficiency, regulatory bottlenecks, and pathway instability. This review provides key case studies and a forward-looking perspective on the evolution of plant synthetic biology as a robust foundation for sustainable biomanufacturing and production of functional biomolecules.